PENGARUH KOMUNIKASI INTERNAL TERHADAP PRODUKTIVITAS PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Rusli, Yenni (PREDIKSI, 2016)
An office could works well marked by the existence of a synergy and harmonious cooperation from various components that are constructed and kept with good communication. This means that when the process of communication between the components can be held in harmony, then the organization is more established and organization performance will increase and grow, and well preserved. The communication could maintain productivity by giving an explanation to the employees about what should be done, how good the thing should be done and what can be done.The purpose of this research is to know how big the influence of Internal Communication can be done to improve the productivity of the employees of Dinas Pekerjaan Umum Kabupaten East Kutai in East KalimantanThe results of research on internal communication is impossible with in Dinas Pekerjaan Umum Kabupaten East Kutai with do communication to the downhill, horizontal communication and communication channel traffic. the results of the tests could be seen clearly that the affect of internal communication variables against the employees work productivity variable. Both variables show significant positive relations it means that the higher the communication result and the employees work productivity also produced.